How to Protect Future Generations Using Tax-Base Restrictions - Rangel, Antonio (American Economic Review, 2005)
This paper studies how to protect future generations from expropriation and to induce optimal investment in intergenerational public goods (IPGs), by introducing constitutional restrictions on the tax base. The type of tax-base restrictions that we consider places limits on the tax instruments that the government can use to raise revenue, but not on the level of expenditures or debt. We show that the introduction of a constitutional amendment requiring that IPGs and debt be financed with land taxes makes intergenerational expropriation impossible and, for many cases of interest, induces optimal investment in IPGs. We also show that a weaker constitutional amendment requiring that IPGs be financed with land taxes, but imposing no restrictions on how to finance the debt, has a positive impact on IPGs, but not on expropriation. The paper also studies the political feasibility of these reforms. We show that the first reform is not politically feasible since it hurts current generations, but the weaker reform can induce a Pareto improvement.